PEMBUATAN SISTEM E-COMMERCE PRODUK MEUBEL BERBASIS KOMPONEN - Kosasi, Sandy (PROCEEDING IC-ITECHS 2014, 2014)
The purpose of the research resulted in E-Commerce system that provides easiness ofcommercial transactions across the boundaries of cultures and countries with relatively more effective cost and serves personal interaction among users. The marketing digitization provides a number of operational advantages such as an easier tracing of data processing of ordering, inventory system and a more accurate payment that can create a good relationship between companies and customers. Methods used to analyze the market expansion are market opportunity analysis, business model design, customer interface, market communications and prototype design. The production of E-Commerce system uses a component-based extreme programming method. E-Commerce system has front-end and back-end. The management system of content specifically negates intermediaries, reduces manufacturing and shipping costs, and stores information. E-Commerce architecture focuses on the component use of CSS (Cascading Style Sheets), PHP (Personal Home Page), Javascript Framework, jQuery, CI (CodeIgniter), and empowers the MVC (Model View Controller). The functional testing was used. The software used to do a functional test is Lime. Lime technique is integrated with the Symphony framework for PHP programming language so it is an easy testing process. The web-based sales information system can significantly expand the market share through a more dynamic and interactive business process and have a clear differentiation pattern for all segments of society.